Mutation of ompA gene of Shigellajlexneri: towards development of an oral live attenuated Shigella vaccine - Lim Meng, Huang (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Shigellosis is one of the major infectious diseases in the world. Each year in developing country, Shigella spp. cause illness in over 150 million individuals and death in over one million (Kotloff et al., 1999). Children under the age of 5 are most severely affected. In developing countries, S. flexneri and S. sonnei are the most prevalent species, causing about 60% and 15% of episodes, respectively. The enormous global burden of Shigella, augmented by the growing rate of antimicrobial resistance, makes development of an effective vaccine essential. At present there is no vaccine against Shigella, although a variety of live and subunit vaccines which elicit an anti-LPS mucosal response have been shown to confer protection in experimental models of shigellosis (Levine et al., 1976; Sanchez et al., 1994; Jennison et al., 2004). Live, attenuated Shigella strains have been the dominant approach to Shigella vaccine development since a 1966 report (Formal et al., 1 966) showing that monkeys were protected against subsequent disease if previously administered attenuated organisms. S . .flexneri poses a structural gene, ompA which encodes tbr outer membrane protein A. Outer membrane protein A adds to the stability of the cell envelope by linking the outer membrane to the peptidoglycan. Therefore, in this study the gene of interest is ompA whereby the gene will be mutated by insertional mutation. The mutants are assumed to induce protective immunity against shigellosis. In this study, ompA has been mutated by using kanamycin resistance gene (aphA). The use of this antibiotic resistance gene is to facilitate the process of manipulating the genes as it serves as a selective marker. The creation of the construct ompA::aphA is to facilitate the approach into the development of a potential live attenuated Shigella vaccine.